Penyakit Daun Keriting Kuning Cabai di Indonesia - Sri Sulandari (Jurnal Perlindungan Tanaman Indonesia, 2006)
The epidemic of pepper yellow leaf curl disease caused by Begomovirus has been observed in Indonesia since 2000. The virus can not be transmitted either by seed or mechanical inoculation. In the laboratory the virus can be transmitted by grafting and in the field, the disease spread over only by Bemisia tabaci Genn as a vector of the disease in persistant .manner. The disease widespread at some pepper production centers in Java,Sumatera, Bali, Kalimantan, and Sulawesi. The epidemic of the disease is influenced by some factors such as, changing of the planting pattern, the influence of global warming, planting of the new susceptible cultivars, and the formation of new virulence strain of Begomovirus. Beside attacking pepper, the virus can infect other plants and weeds that belong to Solanaceae, Compositae and some Leguminosae. The best method to control the disease is by the integrated program such as plantingthe healthy seedling of pepper, sanitation of weeds that grown souronding the pepper plantation, planting the tolerant cultivars of pepper, improving the planting pattern, and controlling the vector of the disease.